Development of a Novel Wasp-Inspired Friction-Based Tissue Transportation Device - Sakes, Aimée; van de Steeg, Ivo A.; de Kater, Esther P.; Posthoorn, Perry; Scali, Marta; Breedveld, Paul (Frontiers in Bioengineering and Biotechnology, 2020)
Currently existing tubular transportation systems for the extraction of large tissue masses during Minimal Invasive Surgery (MIS) are subjected to a large amount of operating limitations. In this study, a novel transportation mechanism (patented) was developed inspired by the egg-laying structure of wasps. The developed mechanism consists of an outer tube within which six reciprocating semi-cylindrical blades are present and tissue is transported using a friction differential between the blades. Two motion sequences were developed: (1) 1–5 motion sequence, in which one blade moves forward, while the remaining five blades move backward and (2) 2–4 motion sequence, in which four blades move backward while two blades move forward. A proof-of-principle experiment was performed to investigate the effects of tissue elasticity, tissue heterogeneity, and the motion sequence on the transportation rate [mg/s], transportation efficiency [%], and transportation reliability [%]. The mean transportation rate and reliability was highest for the 9 wt% gelatine phantoms at 4.21 ± 0.74 mg/s and the 1–5 sequence at 100%, respectively. The prototype has shown that the friction-based transportation principle has the potential of becoming a viable and reliable alternative to aspiration as a transportation method within MIS.